Penerapan Model Pembelajaran Berbasis Kecerdasan Interaksional untuk Meningkatkan Kompetensi Berbahasa Arab Siswa Madrasah Aliyah - Die Bhakti Wardoyo Putro; Siti Rochmiyati Siti Rochmiyati (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
Indonesian language textbooks in junior high schools consist of various genres, one of which is genre description. It is hoped that the description genre will be able to instil character education in students. This study aims to determine the cultivation of character education in Indonesian textbooks, especially genre descriptions. This research is qualitative descriptive research. The data of this research are in the form of phrases, words, clauses, sentences, paragraphs, and discourses that contain the cultivation of character education in Indonesian junior high school textbooks. The data were obtained from Venda Margareta's research (umbrella research) and Indonesian junior high school textbooks. In this study, the research instrument is a researcher who has been equipped with a set of theories and data cards that contain a study of operational verbs in a textbook. The instrument was validated with content validation by experts carried out by language teaching experts. Data collection techniques in this study using documentation techniques and literature study. The validity of the data was carried out by peer checking techniques through discussion or Focus Group Discussion (FGD). Analysis of the data in this study through the process of reduction, data presentation, and leverage. The results of the seventh-grade research show that the application of character education is found in text descriptions and is able to increase the character values ​​of students. The planting of character education found, namely the values ​​of honesty, discipline, responsibility, caring, polite, and confidence.